Analysis of the Constitutional Court's Ruling against the Legalization of Medical Cannabis and its Practice in Maqashid - Lingga, Ahmad Maulana; Irwansyah, Irwansyah (Indonesian Interdisciplinary Journal of Sharia Economics (IIJSE), 2024)
Medicine is one of the most important things in human life. Many substances can be used as medicine, including marijuana. In this case, according to the decision of the constitutional court, permission was not granted for the medical use of marijuana for various reasons. Even though developed countries like America have allowed the use of marijuana as a medicine. Health services in our country can be said to be quite up-to-date in terms of human resources, however when it comes to granting permits to use marijuana as a source it is not permitted either by general law or by religious law. The many opinions and statements from legal observers and religious leaders make this matter still a matter of debate. Some say that the use of marijuana as a medicine is not a problem if it is still under the supervision of health experts and some say it is not yet the time to allow it because marijuana is a class 1 narcotic, which means it has a very high level of dependence on its users. The Constitutional Court also rejected the use of marijuana as a source of health services because human resources in Indonesia have not been able to accept marijuana as a health service tool, considering and considering the widespread use of narcotics freely, and to date, this has not been addressed by the Government.